2017
DOI: 10.1016/j.hrthm.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac activation–repolarization patterns and ion channel expression mapping in intact isolated normal human hearts

Abstract: In the normal human heart, repolarization gradients encompass all axes, without late midmural repolarization. Last activated areas do not repolarize first as previously assumed. Gradients of mRNAs of single ion channel subunits and of ARIs do not correlate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 20 publications
6
29
0
1
Order By: Relevance
“…In addition we used a G Ks gradient related to the activation sequence. A recent study by Opthof et al in 3 explanted normal human hearts has shown quite different patterns of heterogeneity [31]. It cannot be excluded that some results of our sensitivity analysis would have been different in the presence of these different baseline patterns.…”
Section: Limitationsmentioning
confidence: 74%
“…In addition we used a G Ks gradient related to the activation sequence. A recent study by Opthof et al in 3 explanted normal human hearts has shown quite different patterns of heterogeneity [31]. It cannot be excluded that some results of our sensitivity analysis would have been different in the presence of these different baseline patterns.…”
Section: Limitationsmentioning
confidence: 74%
“…The recent study by Opthof et al is unique in that it used detailed RV and LV measurements in all layers [2].…”
Section: Td-tr Slopes In Patients With Heart Failurementioning
confidence: 99%
“…Individual values of the slope of the relation between depolarization and repolarization times in previous studies and in the present one. O = Opthof et al [1,2], F is Franz et al, [18], C1 and C2 are the CABG and aortic stenosis patients, respectively of the Cowan study [4]. All data refer to LV measurements, except in the non-LBBB and LBBB patients, where values from the combined measurements were used.…”
Section: Disclosuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the transmural electrical gradient, there is also evidence of electrical heterogeneity between the apex to base (Autenrieth et al, 1975;Watanabe et al, 1985;Franz et al, 1987) and left to right ventricles of the heart (Durrer et al, 1970;Srinivasan et al, 2016). Indeed, whole heart studies have shown that the T wave is an index of dispersion of repolarization across the whole heart and not due to transmural electrical gradients (Meijborg et al, 2014;Opthof et al, 2017;Srinivasan et al, 2019).…”
Section: Cardiac Ventricular Repolarization and The Surface Ecg T Wavementioning
confidence: 99%